Analisis Hukum dan Ekonomi: Studi Kasus Pembinaan Kemandirian Narapidana - Andi Armansyah Akbar; Musakkir Musakkir (CV. Social Politic Genius (SIGn), 2022)
This study examines and analyzes the effectiveness and efficiency of the convict self-development program in the penitentiary using legal and economic approaches. This study uses empirical legal research methods. The primary data were collected using direct interviews with four informants. While the secondary data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The data obtained in this research were then analyzed using qualitative data analysis methods with a legal and economic approach. The results show four concepts and five principles for conducting legal and economic analysis. Legal and economic analysis shows that the convict self-development program in Class 1 Penitentiary of Makassar is not running effectively and efficiently based on four factors: legal, law enforcement, facilities, and community. Therefore, it is recommended for MoLHR to make Regulations on observation, assessment, and reporting for implementing the convict development. Furthermore, it is recommended that the Director General of Correctional make Regulations on The guidance for implementing Correctional Guardian. In addition, there should be a restoration of regulations related to the role of correctional guardians as certain functional positions in the Penitentiary. In this case, the convict self-development program in the future can be carried out more focused, measurably, and systematically.